Co-designing inclusive landscape management plans to transform agrifood systems: a technical brief - Tilahun, Seifu A.; Atampugre, Gerald; Zemadim, Birhanu; Cofie, Olufunke O. (CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Landscape in Sub-Saharan Africa faces increasing pressure from both anthropogenic activities and climate change. The agrifood system struggles to utilize the landscape's potential. Misconceptions in landscape management practices, such as neglecting socio-ecological and participatory concepts, hinder sustainable development. Socio-ecological landscape management, which integrates social and ecological systems and promotes collaboration among stakeholders, innovation, resilience to risks, resource sustainability, and community satisfaction, is gaining acceptance. This technical note is to describe adaptive, inclusive landscape management plans that are sensitive to both ecological and health metrics and could be incorporated into governmental frameworks. The design process is iterative with 6 steps, incorporating the perspectives of local stakeholders, governance bodies, researchers, and local experts. The pathway culminates in a comprehensive Inclusive Landscape Management Plan (ILMP) that is both actionable and reflective of community needs.